A new circuitry model for electric double layer capacitor - A. Noorden, Zulkarnain (2014)
A new circuitry model, which consists of constant phase elements is proposed to simply describe the charge storage mechanism of an electric double layer capacitor (EDLC). The model is developed based on previously reported experimental data of cellulose- and glass wool-based capacitors measured by electrochemical impedance spectroscopy. As a result, with a considerably small normalized error, the proposed model fitted the experimental data well for the whole frequency range (from mHz to kHz). The model is capable of providing beneficial information on the charge storage mechanism inside the tested capacitors for each frequency region; low, medium and high frequency region separately. Interestingly, the fitted parameters from the model are consistent with the static EDLC parameters; in particular, the specific capacitance (corresponds to double layer capacitance) and internal resistance values attained from dc properties characterization.